(untitled) (International Journal of Physiology, 2019)
Introduction Central hemodynamics has an important role in maintaining appropriate cerebral and other end-organ perfusion and is altered in type2DM. Arterial stiffening is an early phenomenon in patients with type2DM, affecting cardiac function by increasing the cardiac afterload and reducing diastolic coronary artery perfusion, also involving small vessel disease in the brain and subsequent hypoperfusion. Aims and Objectives The aim of present study was to determine whether aortic stiffness affects cardiac function and whether central elastic artery stiffness was associated with cerebral blood flow pulsatility and subsequent, cerebral perfusion in type 2 DM patients. Materials and Method Fifty six patients with type2DM and 60 age-matched healthy volunteers were enrolled. Aortic PWV was measured using non-invasive cardiovascular risk analysis system (Periscope). Cerebral blood flow was measured by using Trans-Cranial Doppler. Results CFPWV of diabetic group showed significantly higher mean values (Group 1=931.00±215.98cm/s Group 2=1241±152.03cm/s) than control subjects (758±151.82). CFPWV was significantly (p value <0.01) increased between two diabetic groups. HbA1c was most significantly correlated to CFPWV (r=1.00, p<0.001) followed by weak correlation between central aortic stiffness quantified by PWV and PI (r=0.5, p>0.01). Conclusion In patients with type2DM, aortic stiffness is significantly associated with pulse pressure, aortic pulse pressure, aortic augmentation pressure as well as with cerebral blood flow pulsatility and subsequent cerebral perfusion, contributing to decreased cardiac function and cerebral hypoperfusion. Aortic PWV and TCD measurement might be useful prognostic marker of cardiac and cerebrovascular disease in type2DM.